Performance evaluation of porous asphalt mixture enhanced with high dosages of cured carbon fiber composite materials. (8th March 2021) - Zhang, Kun; Liu, Yilong; Nassiri, Somayeh; Li, Hui; Englund, Karl
Highlights: High dosages of a newly developed carbon fiber composite stabilizer were used in porous asphalt. Fiber-shaped carbon composites minimized binder draindown and improved infiltration of porous asphalt. Fiber-shaped carbon composites enhanced ductility and crack resistance of porous asphalt. Abstract: This study used newly-developed fiber-shaped reinforcement elements from cured carbon fiber composite materials (CCFCMs), which were produced from accumulated manufacturing scraps from aerospace manufacturing operation with no current reuse. Previous laboratory and field works have demonstrated a prominent performance for porous asphalt (PA) mixtures enhanced by fiber-shaped CCFCMs at the dosage of 0.05% by weight of the mixture. This study assessed higher dosages (0.15%, 0.30%, and 0.45%) of CCFCMs on the strength and durability of PA mixtures. The results showed that the fiber-shaped CCFCMs helped to stabilize asphalt binder during production and facilitate water infiltration. The addition of high dosages of CCFCMs improved ductility and cracking resistance, but compromised indirect tensile strength. Based on the tested dosages in this and previous studies, the recommended maximum dosage of processed CCFCMs used in PA mixtures is 0.15%.